Fardhu Kifayah Learning Media Application Using Android-Based Augmented Reality - Baratih, Ira Iranda Isyha; Fakhriza, M. (Journal of Computer Science and Informatics Engineering, 2025)
Advances in information technology and telecommunications have brought significant changes to the field of education. Technology-based learning media provides an effective solution for improving the quality of learning and student motivation. One of the emerging technologies is augmented reality (AR), which can create interactive and engaging learning experiences. Observations at the Amal Shaleh Islamic Junior High School revealed the need for more interactive, technology-based learning tools. The learning process still relies on conventional methods, such as explanations on the blackboard and textbooks, making it challenging for students to fully grasp the material. The researchers chose the topic "Management of Deceased Bodies" as the focus for developing learning media, given the importance of understanding the procedures for managing corpses according to Islamic law. In fiqh studies, the obligation to care for a corpse is considered a fardhu kifayah, meaning that if one person fulfills this duty, the responsibility is lifted from others. However, if no one performs the task, the entire community bears the sin. Thus, it is crucial for students to understand and apply the procedures correctly. This research employed the Markerless method, and the outcome was an interactive learning medium utilizing augmented reality. The goal of this innovation is to enhance students' understanding of the procedures for handling deceased bodies, enabling them to apply this knowledge within their communities